1998
DOI: 10.1177/088626098013004001
|View full text |Cite
|
Sign up to set email alerts
|

Self-Mutilating Behavior of Sexually Abused Female Adults in Turkey

Abstract: The authors' study included 42 female adult patients. All the patients had been sexually abused by family members. The participants were grouped into two groups: those with self-mutilating behavior (SMB) and those without such behavior. They were evaluated for history of physical and sexual trauma, suicide attempts, eating habits, and SMB. The ratio of SMB in the sample was 33.3%. Our findings support that SMB and sexual abuse are closely related to eating disorders, particularly anorexia. The relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 8 publications
0
22
0
2
Order By: Relevance
“…Common syndrome expressions of the internalizing outcome include depression (Koss et al, 2003;Marshall et al, 2005) and anxiety (Fergusson et al, 2002), including PTSD, which is the most commonly studied psychological outcome following trauma (e.g., Bernat et al, 1998;Kessler et al, 1995). Internalized anger associated with childhood trauma (particularly childhood sexual abuse) is also associated with cutting behaviors, suicidal ideation, and suicidal behaviors (Baral, Kora, Yuksel, & Sezgin, 1998;Low, Jones, MacLeod, Power, & Duggan, 2000). Another form of physical selfpunishment following trauma may be the experience of an eating disorder.…”
Section: Evidence Supporting Topa Model Elementsmentioning
confidence: 98%
“…Common syndrome expressions of the internalizing outcome include depression (Koss et al, 2003;Marshall et al, 2005) and anxiety (Fergusson et al, 2002), including PTSD, which is the most commonly studied psychological outcome following trauma (e.g., Bernat et al, 1998;Kessler et al, 1995). Internalized anger associated with childhood trauma (particularly childhood sexual abuse) is also associated with cutting behaviors, suicidal ideation, and suicidal behaviors (Baral, Kora, Yuksel, & Sezgin, 1998;Low, Jones, MacLeod, Power, & Duggan, 2000). Another form of physical selfpunishment following trauma may be the experience of an eating disorder.…”
Section: Evidence Supporting Topa Model Elementsmentioning
confidence: 98%
“…Although some researchers found a strong association between bulimic symptomatology and impulsive behaviors, including self-injury, others have questioned this association. For instance, one study found a similarly high incidence of self-injury in a group of women with restricting anorexia nervosa (Baral, Kora, Yuksel, & Sezgin, 1998). There may be a more complex relationship between self-injury and eating disorders that is not limited to a direct association with bulimic symptomatology.…”
Section: Introductionmentioning
confidence: 97%
“…One of the reasons of inconsistency is utilization of deliberate self-harm, self-injury and selfmutilation terms to describe the same phenomenon reciprocally (22,(54)(55)(56)(57). Another important problem and factor of inconsistency is using the DSH term to describe behaviors having different nature.…”
Section: Discussionmentioning
confidence: 99%